Vriendschap : maandblad gewijd aan de homofilie. - Cultuur en Ontspanningscentrum (COC) (Amsterdam : COC, 1949)
Fonds Suzan Daniel (FSD)
Ondertitel : wisselend
Periodiciteit : maandelijks
Redactie : COC, Postbus 542, Amsterdam
Nederlands
Periodiek